Normal voice processing after posterior superior temporal sulcus lesion. (October 2017) - Jiahui, Guo; Garrido, Lúcia; Liu, Ran R.; Susilo, Tirta; Barton, Jason J.S.; Duchaine, Bradley
Abstract: The right posterior superior temporal sulcus (pSTS) shows a strong response to voices, but the cognitive processes generating this response are unclear. One possibility is that this activity reflects basic voice processing. However, several fMRI and magnetoencephalography findings suggest instead that pSTS serves as an integrative hub that combines voice and face information. Here we investigate whether right pSTS contributes to basic voice processing by testing Faith, a patient whose right pSTS was resected, with eight behavioral tasks assessing voice identity perception and recognition, voice sex perception, and voice expression perception. Faith performed normally on all the tasks. Her normal performance indicates right pSTS is not necessary for intact voice recognition and suggests that pSTS activations to voices reflect higher-level processes. Highlights: A patient with a lesion to right pSTS was tested with eight voice perception tasks. The patient scored normally on all the voice tasks (identity, sex, emotion). Her performance indicates right pSTS is not necessary for basic voice processing.